Esophagic perforation caused by extraneous elements. - Domínguez, Carlos; Armand Ugon, César; Berazategui, Ruver; Cordero, Miguel (Cirugía del Uruguay, 1984)
Discussion of the management, diagnosis and treatment of esophagic perforations based on tour cases in cervical and superior mediastinum topographic location. Stressed is the prevision value -evidenced by a lower morbimortality- of early diagnosis and treatment, specially if effected within the first twenty-four hours. Surgical treatment is fundamental and must be upholded by a correct metabolonutritional backing extra -oral, plus an adequate antibiotic therapy- for polymicrobial flora.